Gadamer and tolerance: : between unusual virtue and human foundation - Marques Kussler, Leonardo (2024)
The idea of tolerance is central to understanding the current moral and political landscape, as it not only reflects essential human principles, but is also essential for the healthy functioning of democratic and inclusive societies. In this paper, the main objective is to situate tolerance among the main theorists and define it as an aspect present in philosophical hermeneutics. To do so, we divided the text into two main parts. In the first part, we present the main views on the concept of tolerance as a virtue and its paradigmatic condition. In the second part, based on the text The idea of tolerance, by Hans-Georg Gadamer, we contextualize tolerance beyond the conception of virtue, defending it as a fundamentally human and necessary element to rethink the challenges of contemporary times.